Effect of recombinant LH supplementation timing on clinical pregnancy outcome in long-acting GnRHa downregulated cycles - Chenyang Huang; Xiaoyue Shen; Jie Mei; Yanxin Sun; Haixiang Sun; Jun Xing (BMC, 2022)
Abstract Background Timely and moderate luteinizing hormone (LH) supplementation plays positive roles in in vitro fertilization/intracytoplasmic sperm injection and embryo transfer (IVF/ICSI-ET) cycles with long-acting gonadotropin-releasing hormone agonist (GnRHa) pituitary downregulation. However, the appropriate timing of LH supplementation remains unclear. Methods We carried out a retrospective cohort study of 2226 cycles at our reproductive medicine centre from 2018 to 2020. We mainly conducted smooth curve fitting to analyse the relationship between the dominant follicle diameter when recombinant LH (rLH) was added and the clinical pregnancy outcomes (clinical pregnancy rate or early miscarriage rate). In addition, total cycles were divided into groups according to different LH levels after GnRHa and dominant follicle diameters for further analysis. Results Smooth curve fitting showed that with the increase in the dominant follicle diameter when rLH was added, the clinical pregnancy rate gradually increased, and the early  miscarriage rate gradually decreased. Conclusions In long-acting GnRHa downregulated IVF/ICSI-ET cycles, the appropriate timing of rLH supplementation has a beneficial impact on the clinical pregnancy outcome. Delaying rLH addition is conducive to the clinical pregnancy rate and reduces the risk of early miscarriage.